ANALISIS DAMPAK PENYUSUNAN PERATURAN PEMBANGUNAN JANGKA MENENGAH DAERAH (RPJMD) TERHADAP PEMBANGUNAN JANGKA MENENGAH DI KABUPATEN MADIUN TAHUN 2018-2023 - Erlita Cahyasari (Birokrasi Pancasila: Jurnal Pemerintahan, Pembangunan dan Inovasi Daerah, 2022)
A good development process always begins with careful planning, both in terms of mechanisms, processes, systems, and substances. So, with regard to the mechanism, the choice of bottom-up planning is to achieve a participatory planning process (in determining community needs), and substantial (types of needs actually needed by the community). The medium-term development planning document is an elaboration of the vision and mission of the Regent and Deputy Regent of Madiun Regency for the 2018-2023 period, which is stated in Law Number 25 of 2004 concerning the National Development Planning System, concerning the Regional Medium-Term Development Plan (RPJMD), namely the planning document for the next five years period of Document. The regional organization within the Madiun Regency Government is obliged to prepare the 2018-2023 Strategic Plan Amendment by referring to the 2018-2023 Madiun District RPJMD Amendment. The programs listed in the RPJMD document are regional programs. In the preparation of the regional organization Renstra by the Regional Apparatus Work Unit, based on the Amended RPJMD, the Minister of Home Affairs Regulation Number 90 of 2019 concerning Classification, Codification, and Nomenclature of Regional Development Planning and Finance. The objectives, targets, and performance indicators listed in the Madiun Regency RPJMD Amendment Document for 2018-2023 are regional goals, targets, and performance indicators. Regional Apparatus Organizations as implementing agencies, must support the achievement of the goals and objectives set out in the document. In order to increase the effectiveness of the implementation of the RPJMD for the Changes in Madiun Regency in 2018-2023, Madiun Regency is obliged to monitor and evaluate the elaboration of the RPJMD and its indicators in the regional organization Strategic Plan.